Pendekatan K-Means Clustering Metode Elbow Pada Analisis Motivasi Pengunjung Festival Halal JHF#2 - Ragil Satria Wicaksana; Dadang Heksaputra; Toufan Aldian Syah; Finka Febri Nur'aini (Jurnal Ilmiah Ekonomi Islam, 2023)
Research that explores intrapersonal elements as a motivation for consumer decisions to visit a regional halal festival using a computational technique is still very rare. Motivation is one of the intrapersonal components of consumers and becomes a vital construct in the formation of marketing strategies in the context of goods and services. In this study, the mental activity that is the focus of the discussion is the determination of the rational factors considered by visitors as elements that shape people's motivation to attend the Jogja Halal Fest #2, referring to the instrument developed by Crompton and McKay. The method used in this study is the K-means clustering approach, whose results provide identification in the form of clustering patterns of visitor motives at JHF that tend to converge on educational, recreational, and transactional reasons, supported by the findings of a cluster number of 3. This study stimulates the importance of discussing the other motives that have not been explored, such as the position of spirituality, so that they can be used as a consideration for building an effective marketing program, especially those related to targeting visitors in the future (segmentation) and its impact on increasing halal literacy.